2016
DOI: 10.17265/2328-2223/2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Based Electrode Materials for Supercapacitor: Progress, Challenges and Prospective Solutions

Abstract: Carbon-based materials are typical and commercially active electrode for supercapacitors due to their advantages such as low cost, good stability and easy availability. In the light of energy storage, supercapacitors mechanism is classified into EDLCs (electrochemical double layer capacitors) and pseudocapacitors. Multidimensional carbon nanomaterials (active carbon, carbon nanotube, graphene, etc.), carbon-based composite and corresponding electrolyte are the critical and important factor in the eyes of resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 40 publications
0
6
0
2
Order By: Relevance
“…The results showed that there had been an increase in the peak in this range, although it did not show a high peak. This happens because the carbonization temperature is low so that the desired peak cannot be formed when the sample is activated and carbonized 30 .…”
Section: Electrical Conductivity Analysismentioning
confidence: 99%
“…The results showed that there had been an increase in the peak in this range, although it did not show a high peak. This happens because the carbonization temperature is low so that the desired peak cannot be formed when the sample is activated and carbonized 30 .…”
Section: Electrical Conductivity Analysismentioning
confidence: 99%
“…These results revealed a poor electrochemical property of the optimized biochar compared to carbon-based material used for energy storage systems. For example, conventional capacitors supercapacitor and batteries which have values of capacitance in the range of 3.4 -763 F/g (Herou et al, 2018), energy density of 3 -275 Wh/kg (Jian et al, 2016;Thomas et al, 2019), and power density of 1-15 kW/kg (Jian et al, 2016).…”
Section: Characteristics Of Optimized Biocharmentioning
confidence: 99%
“…1,2 Many methodologies have been established to prepare three-dimensional or porous carbons with graphitic walls to achieve high surface area and high conductivity, which are of great importance for electrical double-layer capacitors. 37 The hydrophobic nature and high surface area of carbon-based materials also provide advantages when employed as catalyst supports, which allows better adsorption and diffusion of reactions. 8,9 Among these carbon materials, templated carbon has been prepared using hard templates, such as zeolites and mesoporous silica.…”
Section: Introductionmentioning
confidence: 99%